OPTIMAL RATIO OF MALE AND SEXUAL FEMALE IN THE MATING OF MOINA MACROCOPA (CRUSTACEA, MONIDAE) - Mubarak, A. S.; Jusadi, D.; Junior, M. Z.; Suprayudi, M. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
Moina  macrocopa is a natural feed that can be cultured to producing ephippia as a bioproduct for fish and shrimp larvae feed. The number of males in the population affects the quality and quantity of ephippia produced.  This study was conducted with the purpose of examining the female age in M. macrocopa mating and examining the ratio male-female M. macrocopa in the mating on the quantity and quality of ephippia produced.  The treatment in this research was the ratio male-female sex of   1:30,   3:30,  5:30,  7: 30. 9:30., 12:30,  15: 30.   Male and female sexual offspring  M macrocopa were produced from cultured using a combination of induction factors such as density, feed concentration, kairomones and dissolved oxygen. male and female offspring produced were cultured with a density of 1000 ind/ L.  This mating culture was using a container with a volume of water of 2 ml per individual. The results of this study were indicated that mating M. macrocopa using 70-hour old sexual females resulted in the highest ephippia production.  Mating M. macrocopa with a sex ratio of  9:30  (male and female sexual)  ware resulted in ephippia containing two eggs of 100%, with ephippia hatching degree of 35.4- 38.3%.